Componentwise localization of critical points for functionals defined on product spaces - Precup, Radu (Topological Methods in Nonlinear Analysis, 2021)
A new notion of linking is introduced to treat minima as minimax points in a unitary way. Critical points are located in conical annuli making possible to obtain multiplicity. For functionals defined on a Cartesian product, the localization of critical points is given on components and the variational properties of the components can differ, part of them being of minimum type, others of mountain pass type.